Model predictive control synthesis algorithm based on polytopic terminal region for Hammerstein-Wiener nonlinear systems - Li, Yan; Chen, Xue-yuan; Mao, Zhi-zhong (Journal of Central South University, 2017)
An improved model predictive control algorithm is proposed for Hammerstein-Wiener nonlinear systems. The proposed synthesis algorithm contains two parts: offline design the polytopic invariant sets, and online solve the min-max optimization problem. The polytopic invariant set is adopted to replace the traditional ellipsoid invariant set. And the parameter-correlation nonlinear control law is designed to replace the traditional linear control law. Consequently, the terminal region is enlarged and the control effect is improved. Simulation and experiment are used to verify the validity of the wind tunnel flow field control algorithm.